POTASSIUM CHANNELS IN RENAL PROXIMAL TUBULE - Kovačević, Sanjin D; Nešović Ostojić, Jelena (Medicinski podmladak, 2017)
Potassium channels are a diverse family of membrane proteins and they are present within all cells of the body. They contain two subunits α, which determine the structure of the channel, and β, which can modify the properties of the channel. Those channels are transmembrane proteins that take part in K+ movement across cell membranes via a highly selective pore. The kidneys have crucial role in maintaining total body potassium content, by matching its intake and excretion. In the proximal tubule, K+ absorption is primarily passive and proportional to Na+ and water, so that changes in fluid and potassium transport are closely coupled. Proximal tubular K+ channels are crucial for the maintenance of a hyperpolarized membrane voltage. In leaky epithelia, such as the proximal tubule, the hyperpolarization of the basolateral membrane due to the increase in the K+ conductance of that barrier also results in the hyperpolarization of the apical membrane. They are also involved in regulating cell volume and in recycling potassium across the basolateral membrane. K+ channels of the KCNK and KCNJ gene families have been discovered in the basolateral membrane cell of various species. One of the primary functions of basolateral K+ channels is to recycle K+ across the basolateral membrane for proper function of the Na+-K+ ATPase. Activation by extracellular alkalinization has been associated with a role of TASK-2 in kidney proximal tubule bicarbonate reabsorption. In renal proximal tubules, luminal K+ channels play an important role for restoring the driving force of Na+-coupled transport systems (amino acids, glucose), which depolarize the luminal membrane. Some of these luminal K+ channels are activated directly by the transport-associated depolarization, others are regulated by mediators, second messenger pathways and cell volume. Key words: proximal tubule, potassium, channels